Hadith #524 - Sunan al-Nasa'i - Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Amr bin Hisham Ø¹ÙØ±Ù Ø¨Ù ÙØ´Ø§Ù; Burayda bin al-Husayb; Mkhld bin Yazid al-Quraishi ÙØ®ÙØ¯ Ø¨Ù ÙØ²ÙØ¯ Ø§ÙÙØ±Ø´Ù Ø§ÙØØ±Ø§ÙÙ; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Sunan al-Nasa'i)
âSometimes he (Qatadah, his teacher) narrated it as a Marfuâ report and sometimes he did notâ â âThe time for Zuhr prayer is until âAsr comes, and the time for âAsr prayer is until the sun turns yellow. the time for Maghrib is until the twilight disappears, and the time for âIshaâ is until the night is halfway through, and the time for Subh is until the sun rises.â
Grade:

Hadith #2040 - Sunan al-Nasa'i - Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Harmy bin 'Umarah ØØ±ÙÙ Ø¨Ù Ø¹ÙØ§Ø±Ø© Ø¨Ù Ø£Ø¨Ù ØÙØµØ©; Shu'bah bin al-Hajjaj Ø´Ø¹Ø¨Ø© Ø¨Ù Ø§ÙØØ¬Ø§Ø¬; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Sunan al-Nasa'i)
âWhen Abu Talib was dying, the Prophet came to him and found Abu Jahl and âAbdullah bin Abi Umayyah with him. He said: âO uncle, say La ilaha illallah(there is none worthy of worship except Allah), a word with which I will defend you before Allah.â Abu Jahl and âAbdullah bin Abi Umayyah said: âO Abu Talib, are you turning away from the religion of âAbdul-Muttalib.â Then the Prophet said: âI will keep on asking for Allahâs forgiveness for you unless I am forbidden to do so.â
Grade:

Hadith #3189 - Sunan al-Nasa'i - al-Husain bin Hryth Ø§ÙØØ³ÙÙ Ø¨Ù ØØ±ÙØ«; Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Mahmud bin Ghaylan ÙØÙÙØ¯ Ø¨Ù ØºÙÙØ§Ù Ø§ÙØ¹Ø¯ÙÙ ÙÙÙØ§ÙÙ Ø£Ø¨Ù Ø£ØÙØ¯; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨; Waki' bin al-Jarrah ÙÙÙØ¹ Ø¨Ù Ø§ÙØ¬Ø±Ø§Ø (Sunan al-Nasa'i)
âWhoever spends on a pair (of things) in the cause of Allah will be called in Paradise: âO slave of Allah, here is prosperity.â Whoever is one of the people of Salah, he will be called from the gate of Paradise, Whoever is one of the people of jihad, he will be called from the gate of paradise. Whoever is one of the people of charity, he will be called from the gate of Paradise. Whoever is one of the people who fast, he will be called from the gate of Ar-Rayyan.â Abu Bakr, may Allah be p
Grade:

Hadith #3190 - Sunan al-Nasa'i - Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Harmy bin 'Umarah ØØ±ÙÙ Ø¨Ù Ø¹ÙØ§Ø±Ø© Ø¨Ù Ø£Ø¨Ù ØÙØµØ©; Harun bin 'Abdullah al-Hamal ÙØ§Ø±ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙØ±ÙØ§Ù Ø§ÙØÙØ§Ù; Shu'bah bin al-Hajjaj Ø´Ø¹Ø¨Ø© Ø¨Ù Ø§ÙØØ¬Ø§Ø¬; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Sunan al-Nasa'i)
âThe Messenger of Allah (ï·º) said: âWhoever spends on a pair (of things) in the cause of Allah, the gatekeepers of Paradise will call him from the gates of Paradise (saying): O So-and-so, come and enter!â Abu Bakr said: âO Messenger of Allah, such a person will never perish or be miserable.â The Messenger of Allah (ï·º) said: âI hope that you will be one of them.'â
Grade:

Hadith #4092 - Sunan al-Nasa'i - Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Sunan al-Nasa'i)
âA man came to the Messenger of Allah and said: âO Messenger of Allah, what do you think if someone comes to steal my wealth?â He said: âUrge him by Allah.â He said: âWhat if he persists?â He said: âUrge him by Allah.â He said: âWhat if he persists?â He said: âUrge him by Allah.â He said: âWhat if he persists?â He said: âThen fight. If you are killed you will be in Paradise, and if you kill him, he will be in the Fire.'â
Grade:

Hadith #2611 - Sunan Abi Dawud - Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Muhammad bin Abi Da'ud al-Bghdady ÙØÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø¯Ø§ÙØ¯; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨; Waki' bin al-Jarrah ÙÙÙØ¹ Ø¨Ù Ø§ÙØ¬Ø±Ø§Ø (Sunan Abi Dawud)
The Prophet (ï·º) said: The best number of companions is four, the best number in expeditions four hundred, and the best number in armies four thousand; and twelve thousand will not be overcome through smallness of numbers. Abu Dawud said: What is correct is that this tradition is mursal (i.e. the link of the Companion is missing).
Grade: Sahih

Hadith #2612 - Sunan Abi Dawud - Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Ibrahim bin Muhammad bin al-Harith Ø¥Ø¨Ø±Ø§ÙÙÙ Ø¨Ù ÙØÙØ¯ Ø£Ø¨Ù Ø§Ø³ØØ§Ù Ø§ÙÙØ²Ø§Ø±Ù; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Sunan Abi Dawud)
Sulaiman bin Buraidah reported on the authority of his father. When the Apostle of Allaah(ï·º) appointed a Commander over an Army or a detachment, he instructed him to fear Allaah himself and consider the welfare of the Muslims who were with him. He then said âWhen you meet the polytheists who are your enemy, summon them tone of three things and accept whichever of them they are willing to agree to, and refrain from them. Summon them to Islam and if they agree, accept it from them and refrain
Grade: Sahih

Hadith #4695 - Sunan Abi Dawud - Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Mhmwd bin Khalid ÙØÙÙØ¯ Ø¨Ù Ø®Ø§ÙØ¯; Muhammad bin Yusuf al-Faryabi ÙØÙØ¯ Ø¨Ù ÙÙØ³Ù Ø§ÙÙØ±ÙØ§Ø¨Ù; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Sunan Abi Dawud)
The first to speak on Divine decree in al-Basrah was Ma`bad al Juhani. I and Humaid b. `Abd al-Rahman al-Himyari proceeded to perform Hajj or `Umrah. We said : would that we meet any of the Companions of the Messenger of Allah (ï·º) so that we could ask him about what they say with regard to divine decree. So Allah helped us to meet `Abd Allah b. `Umar who was entering the mosque. So I and my companion surrounded him, and I thought that my companion would entrust me the task of speaking to him.
Grade: Sahih

Hadith #4937 - Sunan Abi Dawud - Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Masdad bin Masrhad ÙØ³Ø¯Ø¯ Ø¨Ù ÙØ³Ø±ÙØ¯ Ø¨Ù ÙØ³Ø±Ø¨Ù; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù (Sunan Abi Dawud)
We came to Medina and stayed with Banu al-Harith b. al-Khazraj. She said : I swear by Allah, I was swinging between two date-palms. Then my mother came down; and I had my hair up to the ears. The transmitter then rest of the tradition.
Grade: Hasan Sahih

Hadith #61 - Jami' al-Tirmidhi - Abdur Rahman bin Mahdi Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù ÙÙØ¯Ù; Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Muhammad bin Bashar Bindar ÙØÙØ¯ Ø¨Ù Ø¨Ø´Ø§Ø± Ø¨ÙØ¯Ø§Ø±; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Jami' al-Tirmidhi)
âThe Prophet would perform Wudu for every Salat. So during the year of the Conquest, he performed all of the prayers with one Wudu, and he wiped over his Khuff. So Umar said, âYou did something that you have not done before?â He replied: âI did it on purpose.â
Grade:

Hadith #152 - Jami' al-Tirmidhi - Ahmed bin Manay' Ø£ØÙØ¯ Ø¨Ù ÙÙÙØ¹; Ahmed bin Muhammad bin Musa al-Samsar Ø£ØÙØ¯ Ø¨Ù ÙØÙØ¯ Ø¨Ù ÙÙØ³Ù Ø§ÙØ³ÙØ³Ø§Ø±; al-Hasan bin al-Sbah al-Bzar Ø§ÙØØ³Ù Ø¨Ù Ø§ÙØµØ¨Ø§Ø Ø§ÙØ¨Ø²Ø§Ø±; Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Ishaq bin Yusuf bin Mrdas Ø¥Ø³ØØ§Ù Ø¨Ù ÙÙØ³Ù Ø¨Ù ÙØ±Ø¯Ø§Ø³; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Jami' al-Tirmidhi)
âA man came to the Prophet to ask him about the times for Salat. So he said: âStay with us, In sha Allah.â So he ordered Bilal to call the Iqamah when Fajr began, then he ordered him to call the Iqamah when the Sun passed the zenith, then he prayed Zuhr. Then he ordered him to call the Iqamah to pray Asr while the sun was elevated and white. Then he ordered him (to call the Iqamah for) Maghrib when the (top) edge of the sun had set. Then he ordered him to call the Iqamah for Isha when the
Grade:

Hadith #1052 - Jami' al-Tirmidhi - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil Ø§ÙØ¶ØØ§Ù Ø¨Ù ÙØ®ÙØ¯ Ø£Ø¨Ù Ø¹Ø§ØµÙ Ø§ÙÙØ¨ÙÙ; al-Hasan bin 'Ali al-Halwani Ø§ÙØØ³Ù Ø¨Ù Ø¹ÙÙ Ø§ÙØ®ÙØ§Ù Ø§ÙØÙÙØ§ÙÙ; Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Mahmud bin Ghaylan ÙØÙÙØ¯ Ø¨Ù ØºÙÙØ§Ù Ø§ÙØ¹Ø¯ÙÙ ÙÙÙØ§ÙÙ Ø£Ø¨Ù Ø£ØÙØ¯; Muhammad bin Bashar Bindar ÙØÙØ¯ Ø¨Ù Ø¨Ø´Ø§Ø± Ø¨ÙØ¯Ø§Ø±; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Jami' al-Tirmidhi)
âThe Messenger of Allah prohibited plastering graves, writing on them, building over them, and treading on them.â
Grade:

Hadith #1394 - Jami' al-Tirmidhi - Abdur Rahman bin Mahdi Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù ÙÙØ¯Ù; Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Muhammad bin Bashar Bindar ÙØÙØ¯ Ø¨Ù Ø¨Ø´Ø§Ø± Ø¨ÙØ¯Ø§Ø±; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Jami' al-Tirmidhi)
that a girl went out in Al-Madinah wearing some silver ornaments. A Jew grabbed her and fractured her head with a stone, and he took the jewelry she had on. He said: âShe was found with some spark of life in her, and was brought to the Prophet (ï·º) and he said: âDid such and such person strike you?â She nodded ânoâ with her head. He said: âSuch and such?â until he named the Jew and she nodded âyesâ with her head.â He said: âHe was brought and recognized so the Messenger of
Grade:

Hadith #1488 - Jami' al-Tirmidhi - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil Ø§ÙØ¶ØØ§Ù Ø¨Ù ÙØ®ÙØ¯ Ø£Ø¨Ù Ø¹Ø§ØµÙ Ø§ÙÙØ¨ÙÙ; al-Hasan bin 'Ali al-Halwani Ø§ÙØØ³Ù Ø¨Ù Ø¹ÙÙ Ø§ÙØ®ÙØ§Ù Ø§ÙØÙÙØ§ÙÙ; Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Mahmud bin Ghaylan ÙØÙÙØ¯ Ø¨Ù ØºÙÙØ§Ù Ø§ÙØ¹Ø¯ÙÙ ÙÙÙØ§ÙÙ Ø£Ø¨Ù Ø£ØÙØ¯; Muhammad bin Bashar Bindar ÙØÙØ¯ Ø¨Ù Ø¨Ø´Ø§Ø± Ø¨ÙØ¯Ø§Ø±; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Jami' al-Tirmidhi)
That the Messenger of Allah (ï·º) said: âIndeed there are others inhabiting your homes. So yell at them three times (to leave). If you see any of them after that, then kill them.â
Grade:

Hadith #1581 - Jami' al-Tirmidhi - Abdur Rahman bin Mahdi Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù ÙÙØ¯Ù; Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Muhammad bin Bashar Bindar ÙØÙØ¯ Ø¨Ù Ø¨Ø´Ø§Ø± Ø¨ÙØ¯Ø§Ø±; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Jami' al-Tirmidhi)
That the Messenger of Allah (ï·º) said: âWhoeverâs soul departs from his body while he is free of three: Kanz (buried treasure), Ghulul, and debt, then he will enter paradise.â This is how Saâeed narrated it: âKanzâ while Abu âAwanah said in his narration: âKibrâ and he did not mention âfrom Maâdanâ in it. But the narration of Saâeed is more correct.
Grade:

Hadith #1809 - Jami' al-Tirmidhi - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil Ø§ÙØ¶ØØ§Ù Ø¨Ù ÙØ®ÙØ¯ Ø£Ø¨Ù Ø¹Ø§ØµÙ Ø§ÙÙØ¨ÙÙ; Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Hassan ibn Ali bin Abi Talib; Mahmud bin Ghaylan ÙØÙÙØ¯ Ø¨Ù ØºÙÙØ§Ù Ø§ÙØ¹Ø¯ÙÙ ÙÙÙØ§ÙÙ Ø£Ø¨Ù Ø£ØÙØ¯; Muhammad bin Bashar Bindar ÙØÙØ¯ Ø¨Ù Ø¨Ø´Ø§Ø± Ø¨ÙØ¯Ø§Ø±; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Jami' al-Tirmidhi)
That âAli said: âEating garlic was prohibited except when cooked.â
Grade:

Hadith #2668 - Jami' al-Tirmidhi - Abdullah bin 'Abdur Rahman al-Daarimi Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø§ÙØ¯Ø§Ø±ÙÙ; Abdur Rahman bin 'Abdullah bin 'Utba Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ØªØ¨Ø© Ø§ÙÙØ³Ø¹ÙØ¯Ù; Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Asim bin 'Ali bin 'Asim Ø¹Ø§ØµÙ Ø¨Ù Ø¹ÙÙ Ø¨Ù Ø¹Ø§ØµÙ Ø¨Ù ØµÙÙØ¨; Burayda bin al-Husayb; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Jami' al-Tirmidhi)
that the Messenger of Allah (ï·º) said: âConvey from me, even if it be an Ayah, and narrate from the Children of Israâil, and there is no harm, And whoever lies upon me purposely, then let him take his seat in the Fire.â
Grade:

Hadith #550 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø£Ø¨Ù Ø´ÙØ¨Ø©; Ali bin Muhammad bin Ishaq al-Tanafasi Ø¹ÙÙ Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¥Ø³ØØ§Ù Ø§ÙØ·ÙØ§ÙØ³Ù; Burayda bin al-Husayb; Maharab bin Dithar ÙØØ§Ø±Ø¨ Ø¨Ù Ø¯Ø«Ø§Ø±; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨; Waki' bin al-Jarrah ÙÙÙØ¹ Ø¨Ù Ø§ÙØ¬Ø±Ø§Ø (Sunan Ibn Majah)
âAnd tall date palms, with ranged clustersâ in the Subh.
Grade:

Hadith #765 - Sunan Ibn Majah - Ali bin Muhammad bin Ishaq al-Tanafasi Ø¹ÙÙ Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¥Ø³ØØ§Ù Ø§ÙØ·ÙØ§ÙØ³Ù; Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Sa'id bin Sinan al-Barjami Ø³Ø¹ÙØ¯ Ø¨Ù Ø³ÙØ§Ù Ø§ÙØ¨Ø±Ø¬ÙÙ; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨; Waki' bin al-Jarrah ÙÙÙØ¹ Ø¨Ù Ø§ÙØ¬Ø±Ø§Ø (Sunan Ibn Majah)
âThe Prophet (ï·º) came to us and led us in prayer in the mosque of Banu âAbdul- Ashhal, and I saw him putting his hands on his garment when he prostrated.â
Grade:

Hadith #1614 - Sunan Ibn Majah - Alqama bin Mrthd Ø¹ÙÙÙØ© Ø¨Ù ÙØ±Ø«Ø¯; Burayda bin al-Husayb; Muhammad bin 'Aabad bin Aadm ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø§Ø¯ Ø¨Ù Ø¢Ø¯Ù Ø§ÙÙØ°ÙÙ; Muhammad bin 'Abdullah bin al-Zubair ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø£Ø¨Ù Ø£ØÙØ¯ Ø§ÙØ²Ø¨ÙØ±Ù; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Sunan Ibn Majah)
Aisha and Ibn Abbas said: âThe Messenger of Allah said: âThere is no marriage except with a guardian.â âAccording to the Hadith of Aishah: âAnd the ruler is the guardian of the one who does not have a guardian. â
Grade:

Hadith #1821 - Sunan Ibn Majah - Baqiyya bin al-Walid bin Sa'aid Ø¨ÙÙØ© Ø¨Ù Ø§ÙÙÙÙØ¯ Ø¨Ù ØµØ§Ø¦Ø¯; Burayda bin al-Husayb; Muhammad bin 'Abdur Rahman ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù ÙÙÙÙ; Sulaiman bin Burayda bin al-Husayb Ø³ÙÙÙØ§Ù Ø¨Ù Ø¨Ø±ÙØ¯Ø© Ø¨Ù Ø§ÙØØµÙØ¨ (Sunan Ibn Majah)
âNo deceased person should be mourned for more than three days, except a woman should mourn for her husband for four months and ten days, and she should not wear dyed clothes, except for a garment of âAsb, and she should not wear kohl or perfume, except at the beginning of her purity, when she may apply a little Qust and Azfar.ââ
Grade: